Mongolia Quarterly, October 2008 - World Bank (Washington, DC, 2017)
The recent worsening of the financial crisis in the United States and the contagion to the world real economy are adding pressures for Mongolia to address macroeconomic imbalances. In particular, the fall in copper prices and the shortage of liquidities worldwide will imply a slowdown of global economic growth, lower copper prices, and reduced foreign direct investment (FDI). The implications for Mongolia, a larger current account deficit, much lower government revenues, and continued large investment needs, will pose significant policy challenges for the new government to maintain growth while lowering inflation. Fiscal tightening will be a key to prevent inflation from permanently affecting expectations and to reduce the current account deficit. This includes no further increase in public wages, no further increase in universal cash transfers, and a prioritized investment program limited to what the absorptive capacity of the economy can bear. Fiscal space should be kept for a targeted social safety net to protect the most vulnerable. Reducing inflation is always painful, but the slower the authorities react, the more protracted the process is, with deeper impact in economic activity, employment and poverty.